Labour Union’s challenges for improving for gig work conditions on food delivery in Japan: a lesson for Malaysia - Yosuke Uchiyama; Fumitaka Furuoka; Md Nasrudin Md Akhir; Li, Jingyi; Lim, Beatrice Fui Yee; Khairul Hanim Pazim @ Fadzim (Penerbit UM, 2022)
The development of technology and the flexibility to work in nontraditional ways has led to the emergence of task-based gig workers and this trend has been spreading across Japan. However, the ambiguity of the legal position on app-based on-demand gig workers has led to inequalities in labour relations. This study examines the labour union actions against the employers and related bodies of the online food delivery platform Uber Eats Union to determine the current status and potential for bargaining. The union has requested collective bargaining on the Uber side, but all requests have been rejected. The admissibility of the union’s actions to improve industrial relations depended on two points: the application of the worker character in the law to the delivery workers and the demand for support from other institutions. In terms of the law, the recognition of the worker status of delivery workers is a significant step towards collective bargaining with firms. The active work of the Uber Eats Union could lead to the formation of new labour unions on other platforms and the empowerment of platform workers. Based on Japan’s experience, this paper also draws some lessons for Malaysia’s gig economy.